Learning from Twentieth Century Hermeneutic Phenomenology for the Human Sciences and Practical Disciplines - Owen, Ian Rory (The Indo-Pacific journal of phenomenology, 2008)
The implications of commonalities in the contributions of five key thinkers in twentieth century phenomenology are discussed in relation to both original aims and contemporary projects. It is argued that, contrary to the claims of Husserl, phenomenology can only operate as hermeneutic phenomenology. Hermeneutics arose within German idealism. It began with Friedrich Ast and Heinrich Schleiermacher and was further developed by, among others, Wilhelm Dilthey and Martin Heidegger. Hermeneutics claims that current understanding is created on the basis of the prior understanding taken to any new situation, in that what is initially understood or believed determines the direction and scope for inquiry or action. Subsequent action and conclustions are similarly based on what has been previously understood and believed. As a consequence, however, what may, in some cases, result is the confirmation of prior inaccurate understanding. For these reasons, it is important to be clear about how initial understandings are formed and how they inform a discipline, be it the Husserlian phenomenology of intentionality or any empirical phenomenological approach.